Artificial intelligence in precision medicine - Menden, Michael P. (Henry Stewart Talks, 2022)
Precision Medicine, Omics technologies, Artificial Intelligence (AI) in Precision Medicine and drug discovery, Benefits of the use of Artificial Intelligence in drug discovery, Challenges in the use of Artificial Intelligence in standard clinical practice